Faktor-Faktor yang Mempengaruhi Kualitas Audit dengan Independensi Auditor sebagai Moderasi - Anita Wahyu Alviani; Taufikur Rahman (Jurnal Akuntansi dan Audit Syariah)
This study aims to determine the effect auditor’s competence, objectivity, religiosity to audit quality with auditor’s independence as the moderating variable of the auditors of Inspektorat Kabupaten Wonogiri, Semarang, dan Kota Salatiga. The population in this research are auditors in three research locations, namely the Inspectorate of Wonogiri Regency, Semarang, and Salatiga City. While the sample in this study was determined by purposive sampling method with the criteria determined by the researcher which was then obtained by 33 auditors. The type of data used is primary data whose data collection uses a questionnaire. The analytical method used is the MRA test. The results showed that the auditor’s competence variable had no effect on audit quality. The objectivity variable partially has a positive and significant effect on audit quality. The religiosity variable partially has a positive and significant effect on audit quality. The result of the MRA test indicate that auditor independence can moderate the effect of auditor competence, objectivity, and feligiosity on audit quality.